School managers' views about school safety from the invitational theory perspective - Cankaya, Ibrahim H. (Academic Journals, 2010)
The aim of this study was to determine the views of primary school managers about how schools can become safer places from the perspective of invitational theory. The study sample included the interview responses of 35 randomly selected primary school managers working in the center of Elazig City in Turkey. The views of school managers were analyzed by using the qualitative data analysis method. School managers' views on people; teachers should do mentoring for students. School manager views on places; classes should be a multi-purpose, schools should have security cameras and first-aid room. School manager views on policies; teachers and students should be evaluated based on their performance, collective management should be dominant in schools. School manager views on programs; schools should take into consideration expectations of families and students, schools should to organize courses for adults. School manager views on process; schools should have alumni association, schools should collaborate with non-governmental organizations.
Keywords: School safety; safe school; invitational theory